Reproductive biology and diet composition of Rhynchobatus laevis (Bloch and Schneider, 1801) (Rhinopristiformes:Rhinidae) from the northern Indian Ocean - Purushottama, G. B.; Raje, Thakurdas, S. G.; Akhilesh, K. V.; Kizhakudan, Shoba Joe; Zacharia, P. U. (Indian Journal of Fisheries, 2020)
Large sized batoids particularly wedgefishes are highly vulnerable to fishing and yet very few studies have been published on their biology. The reproductive biology and feeding habit of the Rhynchobatus laevis (Bloch and Schneider, 1801) collected off the north-west coast of India, Arabian Sea, northern Indian Ocean is presented. A total of 328 individuals, in the size range from 44.0 to 290 cm total length (TL), 300 to 94000 g total weight (TW) were used for the study. The length-weight relationships were significantly different between the sexes (p<0.001). Co-efficients ‘a’ and ‘b’ of the length-weight relationship were estimated as 0.009412 and 2.830218 (r2 =0.979) for females and 0.004032 and 3.031303 (r2 =0.974) for males, respectively. The length-at-maturity (Lm) for females and males was estimated to be 190.0 and 140.0 cm TL, respectively. Number of embryos ranged from 4 to 10 and the size at birth was estimated to range between 44.0 and 50.0 cm TL. Overall sex ratio favoured females (Female:Male = 1.73:1). There was no significant correlation between maternal TL and no. of embryos produced. Dietary analysis of stomach contents (%IRI) revealed that R. laevis fed primarily on teleosts (83.4%) and crustaceans (15.1%). This study provides the detailed biological observation on size, sex composition, lengthat-maturity (Lm), length-weight relationship and diet of R. laevis from northern Indian Ocean which can be used as essential inputs to formulate effective management plans and conservation strategies for this species in the region. Keywords: Elasmobranchs; Embryo; Guitarfish; Length-weight relationship; Length-at-maturity